Budaya Sekolah: Sebuah Strategi Baru dalam Pembentukan Karakter Siswa - Lutfiana, Rose Fitria (Universitas Negeri Malang, 2023)
This study analyzed strategies for building student character in schools through habituation and school culture. This study used a qualitative approach based on the post-positivism philosophy. Data analysis was carried out interactively through several steps: data collection, data reduction, data presentation, and drawing conclusions. The study results showed that the strategies for building student character in schools were divided into development programs, subject integration, and habituation through school culture. Character building with habituation can be done through intracurricular, co-curricular, and extracurricular activities. Student character can be formed if the school organizes intracurricular, co-curricular, and extracurricular activities to the fullest.